2019
DOI: 10.18821/0016-9900-2016-95-10-923-929
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in regions of arctic settlements

Abstract: The composition and the structure of microbial communities in areas of Arctic settlements were studied. The main attention has been given to microscopic fungi. As result of observation of 5 Arctic regions 117 species of microscopic fungi are revealed in soils and anthropogenic substrates. The identification was carried out with the use ofmycological and molecular genetic methods. Most ofspecies belong to the Ascomycotina. Genus Penicillium is characterized by the most species diversity (24 species). Most offun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Even though anthropogenic influence on the abundance and diversity of fungal species at low temperatures is still scarce [65], some studies have indicated that anthropogenic action in the polar region can change the fungal species composition and lead to the propagation of eurytopic species at low temperature [71] including opportunistic pathogens and degraders [72]. In addition, many fungi associated with points near the glacier were mostly saprophytic, and the most distant points showed dominance of cosmopolitan fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Even though anthropogenic influence on the abundance and diversity of fungal species at low temperatures is still scarce [65], some studies have indicated that anthropogenic action in the polar region can change the fungal species composition and lead to the propagation of eurytopic species at low temperature [71] including opportunistic pathogens and degraders [72]. In addition, many fungi associated with points near the glacier were mostly saprophytic, and the most distant points showed dominance of cosmopolitan fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, using a high-throughput new generation sequencing approach, the composition of the Yamal soil microbiome was investigated. Previous studies in this region were restricted by application of conventional microbiological methods (Kirtsideli et al, 2014;Vlasov et al 2014Vlasov et al , 2016Vlasov et al , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…For Ascomycota, the genus Penicillium is distinguished by the largest number of species (twenty-nine species, or 40% of the total number of species). Dominance in the number of species belonging to the genus Penicillium is typical for the peat soils of the plain and mountain landscapes of the Arctic and Subarctic [4,54,74,75].…”
Section: Diversity Of Fungi In Active and Permafrost Layersmentioning
confidence: 99%